الجملة الإسمية في شعر " بانت سعاد " لكعب بن زهير بن أبي سلمى: NOUN SENTENCES IN "BANAT SU'AD" POETRY BY KA'B BIN ZAHIR BIN ABI SALMA - Abdullah Hanani; Abdul Muqit; Abdul Latif Khan (El-Jaudah : Jurnal Pendidikan Bahasa dan Sastra Arab, 2022)
مستخلص البحث: فإن شعر بنات سعاد لكعب بن زهير بن أبي سلمى من أمتع الشعر في عصر الرسول صلى الله عليه وسلم لأنه اول المدح من قريش وتأثر من بعده قرونا أجيال بعد أجيال وهو مؤثر في بردة الإمام البشري. اهتم الباحث هنا البحث من ناحية الجملة الإسمية. استخدم الباحث في هذا البحث المنهج الوصفي الكيفي بنوع الدراسة المكتبية (Library Research)، ومصادر البحث في هذا البحث جمع الكتب والبحث التي تتعلق بالجملة الإسمية . أما نتائج البحث التي حصلها الباحث في هذا البحث فهي: أن الجملة الإسمية في شعر " بنات سعاد " 23 من تركيب المبتداء والخبر ظاهرا كان أو مضمرا، وفي بعض الشعر هناك خبر كان الذي بني بالضم لتفاوق الشعر . وأما من حيث الإعراب أكثرها من الإسم الظاهر ويتكون من العوامل النواسخ التي دخلت المبتداء والخبر مثل كان وأخواتها وإن وأخواتها وظن وأخواتها. الكلمات المفتاحية: الشعر, الجملة, الإسمية, بانت سعاد Abstract: The poetry of “Banat Suad” by Ka’ab bin Zuhair bin Abi Salma is one of the most interesting poetry in the era of the Messenger, may God’s prayers and peace be upon him, because it was the first to be praised by the Quraysh, and it was influenced by him for centuries after generations, and it is influential in the apostasy of the human Imam. The researcher here focused on the research in terms of the nominal sentence. In this research, the researcher used the qualitative descriptive approach by the type of library research, and the sources of research in this research are the collection of books and research related to the nominal sentence. The results of the research obtained by the researcher in this research are: The nominal sentence in the poetry of “Banat Su’ad” 23 is from the structure of the beginner and the predicate, whether apparent or implied, and in some poetry there is a predicate that was built with inclusion to transcend the poetry. In terms of syntax, most of them are from the apparent noun, and it consists of the transcriber factors that entered the beginner and the predicate, such as Kaan and her sisters, An and her sisters, and Thought and her sisters. Keywords: Poetry, Banat Sua’d, Ka’ab bin Zuhair bin Abi Salma